Full‐thickness laparoendoscopic colonic excision in an experimental model. Issue 12 (9th October 2013) - Brigic, A.; Southgate, A.; Sibbons, P.; Clark, S. K.; Fraser, C.; Kennedy, R. H.
<x xml:space="preserve">Abstract</x> Background Patients requiring surgery for complex colonic polyps traditionally undergo colectomy, with significant risks. Typically in excess of 10–30 cm of colon is removed at laparoscopic or open surgery lasting over 60 min. This study details the preclinical development of a rapid, minimally invasive, limited full‐thickness colonic resection. Methods Both survival and non‐survival procedures were performed in anaesthetized 70‐kg pigs. A simulated colonic polyp was created by endoscopic ink injection with a clearance margin delineated by circumferential placement of mucosal argon plasma coagulation marks. Full‐thickness eversion of the bowel was achieved using endoscopically placed anchors and the polyp was excised using a laparoscopic stapler. In survival procedures, pigs were killed under anaesthetic 8 days after surgery. All pigs underwent post‐mortem examination. Results Five procedures were performed (5 pigs). The median (range) procedure duration was 26 (20–31) min, with a specimen diameter of 5·1 (4·5–6·3) cm. The postoperative recovery of survival animals (4 pigs) was uneventful. At post‐mortem evaluation the resection sites were well healed with no evidence of stenosis, intra‐abdominal infection or inadvertent organ damage. Histological assessment of anastomoses showed mucosal repair and restoration of submucosal continuity. Conclusion Full‐thickness localized colonic excision with this technique provides a large specimen with adequate healing in a porcine model. <boxed-text content-type="box" position="anchor" orientation="portrait"> Surgical relevance The number of patients diagnosed with large benign colonic polyps and early node‐negative cancer has increased since the introduction of colorectal screening. Patients unsuitable for endoscopic treatment undergo colectomy and are therefore subject to a significant risk of morbidity and death. This article describes a novel fusion of laparoscopic and endoscopic elements as a potential transformational alternative to current treatment. The eversion full‐thickness laparoendoscopic excision (eFLEX) technique can be performed in under an hour, producing full‐thickness colonic specimens exceeding 5·5 cm in diameter. This technique is suitable for translation into clinical practice as an alternative to hemicolectomy, with the potential for reduced morbidity and cost. </boxed-text> Presented to the Annual Meeting of the Association of Surgeons of Great Britain and Ireland, Glasgow, UK, May 2013; published in abstract form as Br J Surg 2013; 100(Suppl 7): 2